Towards innovations development in the European raw material sector by evolution of the knowledge triangle. (August 2019) - Smol, Marzena; Kulczycka, Joanna
Abstract: The current study presents the importance of collaboration in the knowledge triangle – KT (business, higher education and research) because innovation networks and collaboration are identified in the European Innovation Scoreboard (EIS) as one of the determinants of innovation development in European countries. Moreover, the importance of KT cooperation in the RMs sector is identified as one of the most important factors affecting the development of new innovative solutions (technologies, policies, finance methods, organisation and society). It was also noted that the evolution of the KT in the RMs sector plays an important role in the transition to a circular economy (CE) model in the European Union (EU). Based on a comprehensive review of the available sources and assessment of the tools required for effective collaboration in the KT, a model framework is proposed showing the portfolio of tools supporting the development of KT cooperation in the RMs sector. The model framework includes a specially dedicated platform divided into three main areas of collaboration activity: information, promotion and dissemination, which take into account specified sub-areas. Special attention is paid to the 'inventory of the RM actors' sub-area which presents the innovation performance in the RMs sector, and which should be monitored based on the information collected from internal and external bodies operating in the RMs sector in compliance with the indicators provided in the EIS. The transformation of operating platforms based on the model framework presented could support the development of KT collaboration and the further development of innovation in the European RMs sector.